Konstribusi Muhammad Aṭ-Ṭāhir Ibnu ‘Āsyūr terhadap Maqāṣid Asy-Syarī’ah - Darul Faizin (El-Mashlahah, 2021)
This paper discusses the concept of Ibn ‘Āsyūr's maqāṣid asy-syarī'ah in his renewal of the previous maqāṣid asy-syarī'ah. Based on the results of the author's study, there are some important things that became the idea of renewing Ibn ‘Āsyūr; first: the idea of liberating (istiqlāl) maqāṣid asy-syarī'ah from the discipline of the Uṣūl Fiqh to become a discipline that stands alone. Second: three sources in establishing the maqāṣid asy-syarī'ah, namely; istiqrā', the Qur'an which has clear legal reasons, and the Sunnah mutawātir. Third: maqāṣid asy-syarī’ah has three levels (martabah), namely; definite (qaṭ’iy), approaching definite (qarīban min al-Qaṭ’iy), and conjecture (ẓanniy). Fourth: maqāṣid asy-syarī’ah is divided into two kinds; maqāṣid asy-syarī’ah al-‘ammah and maqāṣid asy-syarī’ah al-khaṣṣah. In the maqāṣid asy-syarī’ah al-‘ammah there are four basic foundations of the Shari'a; fitrah (al-fitrah), moderate (as-samāḥah), egalitarian (al-musāwāh) and freedom (al-hurriyah). Whereas maqāṣid asy-syarī’ah al-khaṣṣah works to implement maqāṣid asy-syarī’ah al-‘ammah in certain laws.Keywords: Ibnu ‘Āsyūr, maqāṣid asy-syarī’ah and uṣul fiqh.Tulisan ini membahas gagasan maqāṣid asy-syarī’ah Ibnu ‘Āsyūr dalam pembaharuannya terhadap maqāṣid asy-syarī’ah sebelumnya. Berdasarkan hasil telaah penulis, ada beberapa hal penting yang menjadi gagasan pembaharuan  Ibnu ‘Āsyūr; pertama: gagasan membebaskan (istiqlāl) maqāṣid asy-syarī’ah dari disiplin ilmu usul fikih menjadi suatu disiplin ilmu yang berdiri sendiri. Kedua: tiga sumber dalam menetapkan maqāṣid asy-syarī’ah, yaitu; istiqrā’, al-Qur’an yang memiliki kejelasan alasan hukum, dan sunnah mutawātir. Ketiga: maqāṣid asy-syarī’ah memiliki tiga tingkatan (martabah), yaitu; pasti (qaṭ’iy), mendekati pasti (qarīban min al-Qaṭ’iy), dan dugaan (ẓanniy). Keempat: maqāṣid asy-syarī’ah terbagi dua macam; maqāṣid asy-syarī’ah al-‘ammah dan maqāṣid asy-syarī’ah al-khaṣṣah. Dalam maqāṣid asy-syarī’ah al-‘ammah terdapat empat pondasi dasar syariat; fitrah (al-fitrah), moderat (as-samāḥah), egaliter (al-musāwāh) dan kebebasan (al-hurriyah). Sedangkan maqāṣid asy-syarī’ah al-khaṣṣah bekerja mengimplementasikan maqāṣid asy-syarī’ah al-‘ammah dalam hukum-hukum tertentu.Kata Kunci: Ibnu ‘Āsyūr, maqāṣid asy-syarī’ah dan uṣul fiqh.